Effect of processing conditions on the optical properties of films based on alginate, caseinate and lemongrass oil. Issue 2 (2nd April 2016) - Riquelme, Natalia; Miranda, Margarita; Matiacevich, Silvia
Abstract : Edible films incorporating active agents allow for increases in the shelf life of food products. The aim was to evaluate the film forming suspensions (FFSs) stability on the physical properties of films based on alginate and lemongrass oil. Sodium caseinate (NaCas) concentration (0.15–0.75% w/w) was modified at pH (4–8) and stirring rate (5000–10, 000 rpm), measuring stability and droplet size, while physical characterizations (color, solubility) were determined for films. Stability increased with the increase of NaCas concentration and a decrease in droplet size. The instability by creaming was mainly observed in basic pH. Addition of NaCas and lemongrass oil affected the color (Δ E 00  > 12) and opacity (>12%), obtaining yellow films. Optimal conditions were NaCas concentration 0.15%w/w, pH 8.0, stirring speed of 7500 rpm, where droplet size, opacity, Δ E 00 and solubility factor were 7.08 µm, 15.64%, 12.25 and 86.23%, respectively. In conclusion, pH and NaCas concentration altered FFS stability, but physical characteristics were not affected, except for the resultant yellow color.